2009
DOI: 10.1152/ajpregu.00388.2009
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid attenuates arthritis-induced muscle wasting acting on atrogin-1 and on myogenic regulatory factors

Abstract: Castillero E, Martín AI, López-Menduiña M, Villanúa MA, López-Calderón A. Eicosapentaenoic acid attenuates arthritis-induced muscle wasting acting on atrogin-1 and on myogenic regulatory factors. Am J Physiol Regul Integr Comp Physiol 297: R1322-R1331, 2009. First published September 9, 2009 doi:10.1152/ajpregu.00388.2009.-Eicosapentaenoic acid (EPA) is an omega-3 polyunsaturated fatty acid that has anti-inflammatory and anticachectic actions. The aim of this work was to elucidate whether EPA administration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 52 publications
(53 reference statements)
5
45
0
2
Order By: Relevance
“…The fact that fenofibrate prevented an arthritis-induced increase in these myogenic regulatory factors can be due to its anti-inflammatory effect. As mentioned above, EPA, a natural ligand of PPARs, prevents arthritis-induced increases in atrogin-1 and MuRF1 (11). However, PCNA, MyoD, and myogenin expression remained elevated in arthritic rats treated with EPA.…”
Section: E796 Ppar␣ Agonist Improves Muscle Wasting In Arthritismentioning
confidence: 82%
See 1 more Smart Citation
“…The fact that fenofibrate prevented an arthritis-induced increase in these myogenic regulatory factors can be due to its anti-inflammatory effect. As mentioned above, EPA, a natural ligand of PPARs, prevents arthritis-induced increases in atrogin-1 and MuRF1 (11). However, PCNA, MyoD, and myogenin expression remained elevated in arthritic rats treated with EPA.…”
Section: E796 Ppar␣ Agonist Improves Muscle Wasting In Arthritismentioning
confidence: 82%
“…Several clinical studies have shown benefits from fish oil and EPA in patients with rheumatoid arthritis (26,50). In arthritic rats, we have reported that EPA administration decreases not only the external signs of inflammation but also arthritisinduced muscle proteolysis (11). Therefore, it is possible that the anticachetic effect of EPA is mediated through PPAR activation.…”
mentioning
confidence: 92%
“…EPA administration prevented the inhibitory effect of arthritis on IGF1 and on its expression in the liver, without increasing body weight gain. The absence of effect of EPA on body weight gain can be due to the fact that EPA does not modify food intake in arthritic rats (Volker et al 2000, Castillero et al 2009b. A lack of effect of EPA on body weight together with a protective effect on muscle has also been reported in dystrophic muscle degeneration (Machado et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that EPA has an anti-inflammatory effect decreasing proinflammatory cytokines (Tashiro et al 1998, Zhao et al 2004) and both cyclooxygenase-2 activity and expression (Hurst et al 2009). Furthermore, EPA is able to decrease joint inflammation in rheumatoid arthritis patients (James & Cleland 1997, Simopoulos 2002) and in arthritic rats (Leslie et al 1985, Volker et al 2000, Castillero et al 2009b. In addition to its anti-inflammatory effect, EPA ameliorates arthritis-induced skeletal muscle wasting by decreasing atrogin-1 and Murf-1 gene expression and also increasing the transcription factors that regulate myogenesis (Castillero et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing, EPA does not appear suitable to prevent cancer cachexia, despite being a good candidate for the treatment of other experimental wasting conditions such as diabetes [37] and arthritis [38]. The different effectiveness of EPA in counteracting the various types of muscle atrophies may depend on the underlying pathogenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%